PARP Inhibition Restores Extrinsic Apoptotic Sensitivity in Glioblastoma - Karpel-Massler, Georg; Pareja, Fresia; Aimé, Pascaline; Shu, Chang; Chau, Lily; Westhoff, Mike-Andrew; Halatsch, Marc-Eric; Crary, John F.; Canoll, Peter; Siegelin, Markus D. (PLOS ONE, 2014)
Background Resistance to apoptosis is a paramount issue in the treatment of Glioblastoma (GBM). We show that targeting PARP by the small molecule inhibitors, Olaparib (AZD-2281) or PJ34, reduces proliferation and lowers the apoptotic threshold of GBM cells in vitro and in vivo. Methods The sensitizing effects of PARP inhibition on TRAIL-mediated apoptosis and potential toxicity were analyzed using viability assays and flow cytometry in established GBM cell lines, low-passage neurospheres and astrocytes in vitro. Molecular analyses included western blots and gene silencing. In vivo, effects on tumor growth were examined in a murine subcutaneous xenograft model. Results The combination treatment of PARP inhibitors and TRAIL led to an increased cell death with activation of caspases and inhibition of formation of neurospheres when compared to single-agent treatment. Mechanistically, pharmacological PARP inhibition elicited a nuclear stress response with up-regulation of down-stream DNA-stress response proteins, e.g., CCAAT enhancer binding protein (C/EBP) homology protein (CHOP). Furthermore, Olaparib and PJ34 increased protein levels of DR5 in a concentration and time-dependent manner. In turn, siRNA-mediated suppression of DR5 mitigated the effects of TRAIL/PARP inhibitor-mediated apoptosis. In addition, suppression of PARP-1 levels enhanced TRAIL-mediated apoptosis in malignant glioma cells. Treatment of human astrocytes with the combination of TRAIL/PARP inhibitors did not cause toxicity. Finally, the combination treatment of TRAIL and PJ34 significantly reduced tumor growth in vivo when compared to treatment with each agent alone. Conclusions PARP inhibition represents a promising avenue to overcome apoptotic resistance in GBM.